Diseño de un plan Estratégico y operativo para la Fundación ESPOIR Centrado en el cuadro de mando integral. - Guzmán Ávila, Diana Margoth (2014)
The People's Solidarity Economy means community sectors, associations, cooperatives and other economic units popular encourage economic and social cooperation of its partners and customers by providing a culture of financial solidarity. These entities can extend the credit environment for small businesses, microenterprises and also with emerging credits that require low-income people who do not have sufficient guarantee to access financing. The present study had intended to make a strategic and operational plan for the ESPOIR Foundation, enabling it to meet its strategic objectives for improvement and expansion. ESPOIR as a Foundation is an operating entity of the People's Solidarity Economy and is intended to serve the public, offering credit to individuals, groups and micro entrepreneurs.